Thermal performance and MHD peristaltic flow of hybrid nanofluid (Au-Ta/Blood) in an asymmetric conduit with electro-osmosis and shape factor effects - K. Thirunavukarasan; G. Sucharitha (Case Studies in Thermal Engineering, 2025)
The latest developments in hybrid nanomaterials have a wide range of applications, including engineering, cooling systems, drug delivery and heat transfer phenomenon enhancement. The current research aims to create a mathematical model for targeted drug delivery systems, applicable in areas like cancer treatment, genetic disorder therapies, and infection management. Considering that, the study examines the magnetohydrodynamic peristaltic transport of Ree-Eyring hybrid nanofluid (Au-Ta/Blood) in an asymmetric channel. The effects of electroosmosis, hall current, heat source, buoyancy effect, viscous dissipation, and shape of nanoparticles have been appropriately taken into consideration. The Debye-Hückel approximation is employed to estimate the Poisson-Boltzmann equation. The lubrication approximation is used to reduce the complexity of dimensionless equations. Further, the homotopy perturbation method (HPM) is implemented to solve the non-linear governing equations. Essential explanations are presented with graphical data that illustrates velocity distribution, temperature distribution, pressure rise, and streamlines for different fluid flow variables. Additionally, the table depicts the Nusselt number. The findings indicated that for ascending values of the electroosmotic parameter (ω), the velocity surges on the left wall, whereas it declines along the right wall of the microchannel. An augmentation of the magnetic parameter declines the velocity profile. Furthermore, the incorporation of a 3 % volume fraction of nanoparticles results in a 2.947 % improvement in heat transmission efficiency at the right wall of the peristaltic channel. Laminar-shaped nanoparticles exhibit an 8.595 % enhancement in heat transfer relative to spherical-shaped nanoparticles at the right wall of the microchannel. The pressure rise (Δp) escalates with the augmentation of the Helmholtz-Smoluchowski velocity parameter (Uhs).